Complex Individual Author’s Poetic Definitions in the Lyrics of M. Rylsky in the 1920 – 1930s - Umantseva, N. F. (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2017)
The article deals with the peculiarities of the formation of artistic definitions in the poetry by M. Rylskyi in the 1920–1930s. Different types of epithet word combination were distinguished and characterized, its emotional and expressive semantics were described, connection between individual author’s phrase and distinctive features of artistic thinking of M. Rylskyi was highlighted. The coloristic range of his poetry was analyzed. Individual author’s use of traditional artistic attributes for Ukrainian philology was emphasized.